Onboard coordinated task planning for multi-satellite autonomous to observe area target - LIU Runzi; DING Xu; WANG Yanni; XIA Wenchao; MU Tao; YANG Qinghai (物联网学报)
The existing multi-satellite autonomous task planning methods lack of considering the integrity of area targets observation, resulting in the waste of a large number of observation resources. To solve this problem, an onboard coordinated task planning for multi-autonomous satellite to observe area targets was proposed. Firstly, a multi-satellite coordinated observation task planning model for area targets was established, and a multi-satellite autonomous coordinated planning framework based on contract network. Subsequently, based on this coordinated framework, the dynamic pricing-based bidding, tendering, and bid evaluation mechanisms were designed to realize the multi-satellite autonomous coordinated planning for the tasks of observing area targets. Finally, the simulation results show that, compared to the traditional multi-satellite coordinated planning method based on single-round bidding contract network and fixed price bidding contract network, the task revenue of the proposed method is increased by 60.40% and 29.07%, respectively.